2019
DOI: 10.1007/s13272-019-00384-3
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft noise generation and assessment: executive summary

Abstract: Based on the outcome of a workshop on aviation noise, this special issue on aircraft noise generation and assessment has been assembled. Invited contributions on preselected topics have been combined into one overall story line about both the aircraft noise generation and its assessment to provide an overview on the state-of-the-art capabilities in this research field (accounting both for modelling and measuring efforts). Although most relevant topics are covered, the editors do not claim that the collection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Minimising noise emissions is another objective of commercial aviation. Aircraft noise depends on the thrust rating, the speed of the propulsion system, the MTOW, the flight controls and the landing gear [84]. Noise predictive modelling is a complex process that requires a detailed propulsion system analysis and CFD simulations; both analyse are outside of the scope of this study.…”
Section: Impact On Aviationmentioning
confidence: 99%
“…Minimising noise emissions is another objective of commercial aviation. Aircraft noise depends on the thrust rating, the speed of the propulsion system, the MTOW, the flight controls and the landing gear [84]. Noise predictive modelling is a complex process that requires a detailed propulsion system analysis and CFD simulations; both analyse are outside of the scope of this study.…”
Section: Impact On Aviationmentioning
confidence: 99%
“…Air traffic and aircraft ground services generate noise, the main source of which are the engines operating in the air and on the tarmac [7,12,59]. Sometimes, increased noise is also the result of efforts to increase the performance of aircrafts [28].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study by M. J. Lighthill suggested that the noise from the exhaust of a jet engine reached values of the eighth power to its exhaust speed, which meant that an increase in the jet exhaust speed would exponentially increase the intensity level of generated noise [6]. The turbofan engine successfully reduced the noise generated by its jet exhaust through increased bypass ratios [1], but instead introduced a new source of characteristic fan noise; fan blades form a core component in the engine's composition and functionality, so the sound signatures generated by the fan blades alone are of the highest degree of interest for this paper. With the recent leaps in aviation technology, the possibility of system and component failures has dramatically decreased [12].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1. Overview of aircraft noise sources[1] Most simply, professionals may be able to judge the state of the engine from experience via inspection or manually determine areas of error from observing changes in known parameters. We may compare measured parameters with known parameters of a 'healthy' engine via modeling.…”
mentioning
confidence: 99%